Cases of Subconjunctival Hemorrhage After a Joy Ride - Tanveer A. Chaudhry, Khabir Ahmad, Roomasa Channa, Sana Shoukat Memon (Pakistan Journal of Ophthalmology, 2008)
Subconjunctival hemorrhage is a benign condition that mostly resolves spontaneously on its own, even though it may be very alarming for the patients. Multiple causes of subconjunctival hemorrhage-including local trauma, acute conjunctivitis and systemic hypertension have been reported in literature1, 2. CASES We report here a series of four cases of subconjunctival hemorrhage that occurred following a gyroscopic ride. During Easter break, a group of 4 college students, two boys and two girls, between the ages of 17-19 years, presented to the outpatient department of Barnsley District General Hospital with red eyes. Couple of hours before presenting at the eye clinic, they reported going on a gyroscopic ride outside a local pub. After the ride, they noticed red patches in white of their eyes (Table 1, Fig. 1).